Kepemimpinan Pendidikan Islam Tokoh Pejuang ( K.H Ahmad Dahlan Dan K.H Wahid Hasyim ) - annisa, mella mella; Gusmaletri, Gusmaletri; Zulfitria, Zulfitria; Hidayat, Rahmad (Peneliti.net, 2026)
This article analysis the concept of leadership in Islam and examines the profile, gait, and The values ​​of Islamic leadership are reflected in two central figures of Islam eform in Indonesia, namely K.H. Ahmad Dahlan and K.H. Wahid Hasyim. K.H. Ahmad Dahlan, the founder of Muhammadiyah, was known for his reformist vision in education and social religion, emphasizing the integration of religion and general scienceas well as social concerns. Meanwhile, K.H. Wahid Hasyim, the son of the founder of Nahdlatul Ulama, played a significant role in the modernization of Islamic education and its integration into the national education system, with a moderate and nation alist approach in the political arena. This research uses a qualitative approach with a literature study method to analyze textual data from the given sources. The results show that Islamic leadership not only adheres to prophetic values ​​such as siddiq, tabligh,amanah, and fathanah, but also demands adaptability to the challenges of the times. The comparison of these two figures shows differences in the focus of contributions, where K.H. Ahmad Dahlan focused more on internal reform of the ummah and educational institutions, while K.H. Wahid Hasyim was more active in the realm of politics and integration of Islamic education in the context of a plural state. Nevertheless, both have a common thread in caring for the progress of the ummah through education, moderation, and national vision.